A Zero-Sum Politics of Identification: A Topological Analysis of Wildlife Advocacy Rhetoric in the Mexican Gray Wolf Reintroduction Project. (July 2019) - Walsh, Lynda
As climate change contracts our environment, bringing human and nonhuman communities into increased contact and conflict over scarce resources, advocacy rhetoric is making a related shift, from raising human awareness of problems "out there" to renegotiating the very boundaries between human and nonhuman communities. This shift—along with the advent of online media, which similarly blurs traditional urban versus rural boundaries between communities—invites us to update classic studies of advocacy rhetoric from the 1990s and early 2000s. Accordingly, this study addresses advocates' use of online media in the Mexican Gray Wolf Reintroduction Project. I reconstruct wildlife advocates' attitudes toward the Project, as expressed online in press releases and blog posts, by using a combination of topology—a method that looks at patterns of topoi (shared beliefs, values, and norms) that a community expresses in a given rhetorical situation—and Kenneth Burke's theories of attitudes and identification. I then compare advocates' attitudes with the attitudes of project administrators and landowners in the reintroduction area, reconstructed in earlier work. I conclude that advocates amplify their identification with allies (chiefly wolves and supportive sectors of "the public") and their alienation from competitors (chiefly public-land ranchers and project administrators) via the creation of "straw attitudes" for these communities that conflict both with their own attitude and with the documented attitudes of these communities. This rhetorical strategy creates a zero-sum political scenario for communication in the Project and recapitulates old political divisions in the southwestern United States. I finish by recommending rhetorical strategies aimed to increase identification, rather than alienation, in the Project and by showing what online advocacy rhetoric can teach us about the structure of Burkean theories of identification.